The burden of proof in arbitration - Gebran, Luiza de Macedo; Ribeiro , Marcia Carla Pereira (Revista Jurídica Cesumar: Mestrado (Online), 2025)
This article aims to establish the appropriate rule regarding the burden of proof in arbitration, given the importance of evidence production in this alternative dispute resolution method. The main goal is to understand the rules and determine the most suitable one for application. The deductive method was used, based on a bibliographic review of principled texts and arbitration manuals, along with qualitative analysis of decisions to annul arbitration awards due to the allocation of the burden of proof. As a result, indicators were established for deciding on burden of proof rules. Firstly, the burden of proof derives from the Due Process of Law Principle. Secondly, the effects of the burden of proof within the arbitration procedure are analyzed. Thirdly, the applicability of the Actori Incumbit Probatio rule is evaluated. Fourthly, a comparative study between common and civil law traditions is necessary. Lastly, it is concluded that applying the actori incubit probatio rule is most appropriate for arbitration, minimizing the risk of award annulment.